Kuby immunology - Owen, Judith A; Punt, Jenni; Stranford, Sharon A (England : WH Freeman, 2013)
Presenting current concepts in an experimental context, kuby immunology has been thoroughly updated to include a new chapter on innate immunity, a capstone chapter on immune responses in time and space, and many new focus boxes drawing attention to exciting clinical, evolutionary and experimental connections that help bring the material to life.
Appendix A-1-29p.; Appendix B-1-6p.; Appendix C-1-2p.; Glossary G-1-20p.; Index I-1-29p.
Keywords: Cell development; Immunodeficiency disorders; Innate immunity